2014
DOI: 10.1186/1471-2334-14-245
|View full text |Cite
|
Sign up to set email alerts
|

Urine real-time polymerase chain reaction detection for children virus pneumonia with acute human cytomegalovirus infection

Abstract: BackgroundHuman cytomegalovirus (HCMV) is an important pathogen of viral pneumonia in children. The diagnosis of acute HCMV infection is complicated and difficult.MethodsClinical and laboratory data of 6063 hospitalized children with respiratory infection and 509 with respiratory virus infection alone were retrospectively analyzed. Urine and respiratory specimens of 186 hospitalized children with pneumonia were also prospectively collected. Real-time polymerase chain reaction (PCR) and a chemiluminescent assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…A previous study suggested that children aged <6 months are the major population among HCMVinfected children with pneumonia. 17 During our two-year prospective study, the epidemiological data showed that children aged under one year were the most susceptible population with a peak incidence among the children in the age range of three months to one year. Among all HCMVpositive children, the proportion of the children aged <6 months was 68.7%, whereas that of those aged above 6 months was 31.3%.…”
Section: Discussionmentioning
confidence: 81%
“…A previous study suggested that children aged <6 months are the major population among HCMVinfected children with pneumonia. 17 During our two-year prospective study, the epidemiological data showed that children aged under one year were the most susceptible population with a peak incidence among the children in the age range of three months to one year. Among all HCMVpositive children, the proportion of the children aged <6 months was 68.7%, whereas that of those aged above 6 months was 31.3%.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies have been conducted on the prevalence of HCMV in paediatric population in China and other parts of the world . The results were inconsistent, due to different inclusion criteria, test methods and specimens resources.…”
Section: Discussionmentioning
confidence: 99%
“…For example, viral cultures waste time and energy 11, and nucleic acid testing requires special equipment and high costs 12, 13. Furthermore, antibody testing is unsatisfactory because the CMV antibody has a short lifetime and interferences in the tests 14, 15. The CMV pp65 antigen emerges during the early stages of a CMV infection and is widely distributed in human vascular endothelial cells, peripheral blood leukocytes and human body fluids[16].…”
Section: Introductionmentioning
confidence: 99%